PEMAHAMAN DAN DUKUNGAN SUAMI TERHADAP KEIKUTSERTAAN IBU MENJADI AKSEPTOR KB IUD DI KECAMATAN SECANGGANG LANGKAT - Surya Anita; Dewi Rismauli Bancin; Friska Sitorus (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2021)
The decrease in TFR (Total Fertility Rate) will be closer to the condition of the population growing in balance, a strategy is needed in the implementation of the family planning program. Activities that can be carried out are promoting long-term effective contraceptive methods. This study aims to determine the understanding and support of husbands for the participation of mothers in becoming IUD KB acceptors in Secanggang District, Langkat Regency. The research design used in this study was an analytical survey with cross sectional approach. The sample in this study was 30 respondents who came and wanted to do family planning. The data analysis used was univariate and bivariate analysis. The results of this study indicate that there is a significant relationship between Husband's understanding of the participation of mothers in becoming IUD family planning acceptors in Secanggang District, Langkat Regency, with a pvalue of 0.000. And there is a significant relationship between the husband's support for the participation of mothers in becoming IUD family planning acceptors in Secanggang District, Langkat Regency with a p value of 0,000. It is hoped that it can increase respondents' knowledge about contraceptives so that they can support and understand their wives in choosing contraceptives. Keywords: Understanding, Support, IUD